PENGARUH MOTIVASI, SELF EFFICACY DAN PENGETAHUAN PAJAK TERHADAP MINAT BERKARIR SEBAGAI KONSULTAN PAJAK - Dessyana Renarningtyas; Andri Waskita Aji; Nur Anita Chandra Putry (LPPM STIE YKPN Yogyakarta, 2024)
This study was carefully designed to examine the impact of motivation, self-efficacy, and tax knowledge on interest in a career as a tax consultant. This research is a quantitative study that uses primary data through distributing questionnaires and utilizing non-probability techniques with purposive sampling method. The questionnaire was created through the google form feature and applied measurements by utilizing a Likert scale. Respondents consisted of accounting students of Sarjanawiyata Tamansiswa University. Validity and reliability tests were used to test the data. By utilizing the SPSS version 25 application, multiple linear regression analysis was used to test the hypothesis. Data processing findings show that (1) motivation has a positive effect on career interest as a tax consultant, indicated by tcount> ttable (3.119> 1.985) and significance value (0.002 < 0.005); (2) self efficacy has a positive effect on career interest as a tax consultant, as evidenced by the tcount> ttable (3.049> 1.985) and the significance value (0.003 <0.005); and (3) tax knowledge has a positive effect on career interest as a tax consultant, as evidenced by the tcount> ttable (2.918> 1.985) and the significance value (0.004 <0.005).